How Can Intergroup Interaction Be Bad If Intergroup Contact Is Good? Exploring and Reconciling an Apparent Paradox in the Science of Intergroup Relations. (May 2015) - MacInnis, Cara C.; Page-Gould, Elizabeth
The outcomes of social interactions among members of different groups (e.g., racial groups, political groups, sexual orientation groups) have long been of interest to psychologists. Two related literatures on the topic have emerged—the intergroup interaction literature and the intergroup contact literature—in which divergent conclusions have been reported. Intergroup interaction is typically found to have negative effects tied to intergroup bias, producing heightened stress, intergroup anxiety, or outgroup avoidance, whereas intergroup contact is typically found to have positive effects tied to intergroup bias, predicting lower intergroup anxiety and lower prejudice. We examine these paradoxical findings, proposing that researchers contributing to the two literatures are examining different levels of the same phenomenon and that methodological differences can account for the divide between the literatures. Further, we introduce a mathematical model by which the findings of the two literatures can be reconciled. We believe that adopting this model will streamline thinking in the field and will generate integrative new research in which investigators examine how a person's experiences with diversity unfold.